Hydroxybenzothiazoles as new nonsteroidal inhibitors of 17β-hydroxysteroid dehydrogenase type 1 (17β-HSD1). - Alessandro Spadaro (Public Library of Science (PLoS), 2012)
17β-estradiol (E2), the most potent estrogen in humans, known to be involved in the development and progession of estrogen-dependent diseases (EDD) like breast cancer and endometriosis. 17β-HSD1, which catalyses the reduction of the weak estrogen estrone (E1) to E2, is often overexpressed in breast cancer and endometriotic tissues. An inhibition of 17β-HSD1 could selectively reduce the local E2-level thus allowing for a novel, targeted approach in the treatment of EDD. Continuing our search for new nonsteroidal 17β-HSD1 inhibitors, a novel pharmacophore model was derived from crystallographic data and used for the virtual screening of a small library of compounds. Subsequent experimental verification of the virtual hits led to the identification of the moderately active compound 5. Rigidification and further structure modifications resulted in the discovery of a novel class of 17β-HSD1 inhibitors bearing a benzothiazole-scaffold linked to a phenyl ring via keto- or amide-bridge. Their putative binding modes were investigated by correlating their biological data with features of the pharmacophore model. The most active keto-derivative 6 shows IC₅₀-values in the nanomolar range for the transformation of E1 to E2 by 17β-HSD1, reasonable selectivity against 17β-HSD2 but pronounced affinity to the estrogen receptors (ERs). On the other hand, the best amide-derivative 21 shows only medium 17β-HSD1 inhibitory activity at the target enzyme as well as fair selectivity against 17β-HSD2 and ERs. The compounds 6 and 21 can be regarded as first benzothiazole-type 17β-HSD1 inhibitors for the development of potential therapeutics.